Simultaneous inhibition of multiple steps in the processing of N-linked oligosaccharides does not impair immunoglobulin secretion from rat hybridoma cells - Hashim, Onn Haji; Cushley, W. (1988)
The effects of inhibiting selected pairs of oligosaccharide-processing activities upon the secretion of IgM and IgG molecules have been investigated. In the presence of castanospermine (CSP) plus swainsonine (SW) or deoxynojirimycin (dNM) plus deoxymannojirimycin (dMM), secretion of IgM and IgG from rat hybridoma cells was unimpaired relative to control cultures. The structures of the N-linked oligosaccharides found on the Ig heavy chains isolated from treated cells or culture supernatants were shown to be qualitatively different from those associated with control Ig by persistent sensitivity to digestion by endo H. Furthermore, the electrophoretic mobilities of mu and gamma chains on SDS-PAGE derived from treated cells were consistently slower than those of control heavy chains. IgM and IgG were also efficiently secreted when all glucosidase and mannosidase activities were blocked, and the secreted heavy chains bore endo H-sensitive oligosaccharides. The data suggest that Ig secretion from hybridomas can proceed in the absence of N-linked oligosaccharide processing.